ANIMATION MEDIA DEVELOPMENT BASED MULTIPLE REPRESENTATIONS ON MATERIAL FACTORS AFFECTING CHEMICAL EQUILIBRIUM - amanda maria meirina; Noor Fadiawati; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This researchaims to developmentchemical equilibriumanimation mediabased multiple representation. The researchbeginsby analyzingthe needsatseveral high schools inthe city ofBandarLampungto determinethe need forthe developmentof learninganimationmedia.Furthermore, the authorsdo product developmentin the form ofanimationmediabased multiplerepresentations. The resulting product isthen validatedby an expertdevelopercontent and designto determine thesuitability ofthe content, readability and attractivenessofdesignmediadevelopedlearninganimation. To test thesuitabilityaspect ofcontent,readability anddesignkemerarikananimatedmediaare developed, thenvalidatedbyexperts.Based on thevalidation ofthesuitability ofthe materialaspects ofanimationmedia-based learning multiplerepesentasion materialfactorsaffectingchemical equilibriumrated excellentwithan averagescore of4.88. As for thevalidation ofthedesignaspects oflegibilityand attractivenessmediaanimationrated excellentwithan averagescore of4.73. To determine theresponsesof teachersandstudents towardslearningdevelopedmediaanimationdonelimited testingat a schoolin the town ofBandarLampung. Based onlimited testingthat has beendonecan be concludedthatlearninganimationmediacan enhancestudent interestandmayassist students inmasteringconceptsin particularon materialfactorsaffectingchemical equilibrium. keywords: animation media, chemical equilibrium, multiplerepresentations